Dual Orthogonal Feed Circular Polarization Array Antenna Using Microstrip Slot Feed Network - Quazi Delwar Hossain; Muhammad Asad Rahman; Md.Azad Hossain (Institute of Advanced Engineering and Science, 2015)
This paper presents a new circularly polarized microstrip array antenna using dual-orthogonal feed technique. The feed network for 1x2 array is designed using microstrip lines and slot lines by applying double-sided MIC concept effectively. 90 degree phase difference between two orthogonally feed signals os created by choosing appropriate feed point in the feed network to advance one of the feed signals by quarter wavelength (lemda/4) from other. Excellent radiation performance is obtained from this proposed antenna with low cross polar component. The impedence (<-10dB) bandwidth of the array is 9.1% and the 3-dB axial ration bandwidth is 1.85% (9.905GHz to 10.09 GHz). The average gain is higher than 9dBiC over the 3-dB AR bandwidth. The relation between antenna dimensions and characteristics ia also investigated with a parametric analysis of the antenna.